ENVIRONMENTAL CONCERNS OF HYDRAULICALLY FRACTURING A NATURAL GAS WELL (Utah Environmental Law Review; Vol 32 No 1 (2012))
800x600 Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} This Article explores whether the natural gas drilling process of hydraulic fracturing in shale gas formations causes drinking water contamination or creates additional environmental concerns. Section I lays the groundwork of the geology and history of shale gas and the history of hydraulic fracturing. Section II describes the drilling and hydraulic fracturing stimulation process of a natural gas well. Section III addresses federal regulation of natural gas exploration and production, followed by section IV, which surveys state regulations (Texas, New York, and Pennsylvania). Section V discusses Range Resources and the Railroad Commission of Texas versus the Environmental Protection Agency regarding the alleged contamination of a drinking water well in the Barnett Shale. Section VI delineates Congressional legislation facing hydraulic fracturing. Section VII discusses six key studies on hydraulic fracturing. Finally, Section VIII discusses the environmental concerns facing hydraulic fracturing and the industry's response to such concerns.